Qualitative Job Insecurity and Voice Behavior: Evaluation of the Mediating Effect of Affective Organizational Commitment - Lopez-Bohle, S; Muñoz-Medina, L (SAGE PUBLICATIONS LTD, 2023)
Using social exchange theory as the foundation, this research examines the consequences of qualitative job insecurity on voice behavior, considering the indirect effect of affective organizational commitment. The hypotheses raised are tested using data drawn from a sample of 137 employees of a retailer in Chile at three time points. Workers with high qualitative job insecurity reported lower affective organizational commitment, which in turn decreased their voice behavior. Organizational leaders could encourage employee voice behaviors by reducing their perceptions of qualitative job insecurity and increasing their affective organizational commitment.